Penerapan Strategi Manajemen Konflik dalam Sengketa Pasca Pemilu: Studi Kasus Desa Lamaksenulu, Indonesia - Made Ngurah Demi Andayana; Ernestus Holivil; Adriana Rodina Fallo (Research and Development Agency Ministry of Home Affairs, 2024)
Post-election conflicts in Lamaksenulu Village, Indonesia, reflect public dissatisfaction with election results and underlying socio-political tensions. This study examines conflict management strategies in the context of Thomas and Kilmann’s conflict management theory within a rural Indonesian setting. Adopting a descriptive qualitative approach, the study examines how collaboration, compromise, and accommodation—mediated by traditional leadership and hybrid governance—were used to address disputes. Although reconciliation was pursued through deliberation and dialogue, structural dissatisfaction remains, posing risks of recurring tensions. This research contributes to the literature by localizing a widely used Western conflict management model, offering a culturally grounded perspective on post-election conflict resolution. It demonstrates how combining formal institutions with indigenous practices enhances understanding of conflict dynamics in rural democracies. Key recommendations include improving electoral transparency, strengthening traditional leadership in dispute mediation, and developing inclusive reconciliation programs to foster lasting socio-political stability.